Forty Years of China-Angola Relations: Rethinking the Strategic Partnership - leandro, F.; Yichao, L.; Costa, C. M. (The Palgrave Handbook on China-Europe-Africa Relations, 2025)
The year 2023 marks 40 years since diplomatic relations were established between Angola and China, as well as 20 years since the creation of Forum Macao, and 10 years since the inception of the Belt and Road Initiative. In January 2023, Chinese President Xi Jinping said that “he attaches great importance to the development of China-Angola relations, and stands ready to work with President Lourenço to take the 40th anniversary of the establishment of diplomatic relations between the two countries as an opportunity to deepen political mutual trust, strengthen mutually beneficial cooperation, and enhance people-to-people friendship, so as to write a new chapter in the robust development of the China-Angola strategic partnership” (MFA/PRC, 2023). Indeed, 2023 provides a timely opportunity to evaluate Sino-Angolan relations. It was the Bandung Conference of 1955 that laid the foundation for Sino-Angolan relations: China became involved in South-South relations and began to support self-determination movements against Portuguese colonialism (between 1961 and 1975, China was backing the Popular Movement for the Liberation of Angola (MPLA), National Union for the Total Independence of Angola (UNITA) and National Front for the Liberation of Angola (FNLA) against Portuguese colonial rule). In the pre-independence period, however, political and military cooperation between China and Angola were hindered not just by the Cold War but more importantly by the close relationship between the MPLA and the Soviet Union (the Soviet Union represented a kind of “advanced technological modernity embodied in its military technology”; to the Angolans, only the Soviet Union could provide weapons necessary to ensure a favorable outcome of their war (Telepneva in Cold War liberation—The Soviet Union and the collapse of the Portuguese empire in Africa (1961–1975). The University of North Carolina Press, 2021, p. 201). At the onset of the Angolan sovereign state in November 1975, the MPLA was its ruling party, but the country subsequently slumped into a long, violent civil war fought between the MPLA, UNITA and FNLA. Because China had also supported the UNITA and FNLA during the war against Portugal, official establishment of relations between the MPLA-ruled Angola and China was hampered (even though it cannot be ascertained whether China continued to support UNITA and FNLA into the Angolan civil war: Campos and Vines (2008) and Corkin (2011) have suggested that military support indeed continued, but James (A political history of the civil war in Angola, 1974–1990. Routledge, 2017, p. 68) disagrees categorically, arguing that China was beginning to find itself in a delicate political position with South Africa, and therefore—in order not to exacerbate the situation—opted to assume neutrality regarding Angola, despite continuing to vilify the Soviet presence there). Consequently, not until 1983 did China establish official diplomatic relations with Angola. Between 1983 and 2022, Sino-Angolan relations were driven (directly or indirectly) by cooperation in defense and trade. It is in this particular context that in 2010 China and Angola established a strategic partnership. Ultimately, Sino-Angolan relations are part of China’s wider African policy to access and acquire resources and markets, to export, to secure and diversify supply sources, to win strategic allies and to increase its world status and capacity to influence international politics (Kachiga in China in Africa—Articulating China’s Africa policy. Africa World Press, 2013, p. 55). The purpose of this chapter is to decode what President Xi calls a “new chapter” of Sino-Angolan relations in January 2023. What does a “new chapter” in the context of China and Angola’s strategic partnership entail? To answer the question, our analysis divides Sino-Angolan relations into four phases: Phase 1 (⨠1960–1983), during which relations were asserted under the self-determination principle; Phase 2 (1983–2002), which was a period of cooperation in defense and the MPLA’s external legitimization; Phase 3 (2002–2022), in which the MPLA legitimized itself domestically, Angola was rebuilt, and oil entered the scene; and Phase 4 (2023⨠), which is when a new cooperation model is in the process of being developed. The research is primarily qualitative, and, due to a scarcity of academic sources, a triangulation of primary and secondary sources is adopted.